STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANGANI ANAK INKLUSI DI SD HJ ISRIATI BAITURAHMAN 1 SEMARANG TAHUN 2018 - Musthofiyah, Azzah Nor; Sholihah, Hidayatus (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2019)
This study aims to describe how the strategy of Islamic Education teachers in handling inclusion children in SD Hj Isriati Baiturahman 1 Semarang which consists of: planning, learning process, and evaluation or handling carried out by the Islamic Religious Education teacher right when studying at SD Hj Isriati Baiturahman 1 Semarang.               The research conducted by the author is qualitative research. The research subjects were Islamic Education teachers who taught inclusion children from class I to class VI and collaborated with Counseling Guidance teachers. While the object of this research is the right strategy for inclusion children in Islamic Education subjects. Data is carried out through observation, interviews, documentation. The validity of the data used is Triangulation. Analysis of the data used is Reduction, Display, Conclusing Drawing.               This research is intended to answer the problem: How is the strategy of Islamic Education teachers in handling inclusion children in SD Hj Isriati Baiturahman 1 Semarang. This study shows that: (a) planning of personal records is carried out to Islamic Religious Education teachers with data obtained from homeroom teachers who are followed up by Counseling Guidance teachers. This makes it easy for Islamic Education teachers to plan treatment strategies before learning takes place for inclusion children with various characteristics in different classes. (b) For the implementation of learning carried out in various classes, Islamic Education teachers are assisted by Shadow or accompanying teachers. (c) the handling or evaluation of the study that the strategies of the four Islamic Education teachers have strategies that vary according to the level of characteristics of the inclusion child (Slow Learner, ADHD, mentally disabled). Keywords : inclusion, Islamic Studies Teacher, strategy